EduTrust: A Blockchain-Powered Bridge for Seamless Academic Verification between Institutions and Employers - Kumar, Pankaj; Dandin, Chinmaya; Sumanth, Akshali; Manoj; A R, Darshan (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
In a paradigm shift for academic record management, our groundbreaking system introduces a blockchain-based result verification system for university students, offering unparalleled transparency, security, and efficiency. Deployed on the Blockchain, this innovative solution not only simplifies result management but addresses a pressing industry concern- the challenging process and excessive costs associated with employers verifying student academic trajectories. By leveraging the decentralized and tamper-proof nature of blockchain technology, the system enables employers to authenticate academic records seamlessly and securely, eliminating the need for costly third-party agencies.